Incidence of periventricular leukomalacia in preterm very low birth neonates – A tertiary care experience - Mohd Irshad; Saika Bashir; Waseem Iqbal; Mohd Ashraf (Indian Journal of Child Health, 2020)
Background: The periventricular leukomalacia (PVL) is the most common white matter injury in preterm very low birth weight (VLBW) neonates. It occurs due to ischemic injury to developing oligodendrocytes. It can be detected by cranial ultrasonography (CUS). Objective: The objective of the study was to find incidence of PVL in preterm VLBW babies and its correlation with gestational age, birth weight, and arterial blood PH. Materials and Methods: A total of 80 preterm low birth babies admitted in our neonatal intensive care unit over 1 year were included who met the inclusion criteria. All babies were subjected to CUS starting from the 1st week of their life and repeated weekly by trained radiologist to find changes suggestive of PVL till clinically indicated or normal scan on the 14th day of life. Results: Among 80 preterm low birth babies in our study, 54 (67.5%) were male and 26 (32.5%) were female. Three babies had gestational age of 30 weeks or less, 25 had gestational between 30 and 32 weeks, 35 had gestational age between 32 and 34 weeks, while 17 had gestational age more than 34 weeks. A total of 62 (77.5%) were born through normal vaginal delivery and 18 (22.5%) were born by cesarean section. The incidence of PVL was 2.5%. The most common change was periventricular flare. The incidence of PVL was more in extreme preterm and those with PH <7.2. The mortality was 50% in babies with PVL. Conclusion: The incidence of PVL in preterm low birth weight babies is 2.5% with a mortality of 50%. Prevention and early detection are the keys to mitigate the effects of this disastrous complication of prematurity.